Maternal Coping Strategies for Premature Infant: A Systematic Review - Kapti, Rinik Eko; Arief, Yuni Sufyanti; Triharini, Mira; Saidah, Qori'ila; Azizah, Nurona; Supriati, Lilik (Kesmas, 2022)
A mother’s stress due to the birth of her premature baby results in obstacles to the mother’s role, hence it requires appropriate coping strategies. This review aimed to identify coping factors, explore coping strategies by mothers with premature babies, and identify interventions for enhancing maternal coping strategies. The article navigation utilized Boolean Operator of "or" and "and" with keywords of [preterm or premature or LBW, coping, and mother. Databases included ScienceDirect, EBSCOhost, PubMed, SAGE, ProQuest, and Scopus. The 529 articles obtained were screened by reading the focus of journals and addressing the topic and suitability of the journal content, selecting 10 articles. The first result reported factors influencing coping strategies: delivery method, income, available information, knowledge, support, and maternal self-efficacy. The second result presented maternal coping strategies for closely handling premature babies: belief in God, support-seeking, and the babies’ condition progress. The third result showed two interventions: mother’s empowerment program and group discussions with health workers. These two interventions to improve coping strategies play an important role in supporting mothers by facilitating their participation in caring for their babies.